Desain Mesin Penghancur (Shredder Machine) Batang Kelapa Sawit Berbasis Metode Design For Manufacture and Assembly (DFMA) - Roni Wandra; Yohanes Yohanes; Mustafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
DFMA is defined as the design of a product or component which can facilitate the process of manufacturing and assembly process with other components to become a unified product. The utilization of palm oil is only limited to the fruit to produce oil, and to a certain extent the utilization of fiber fruit bunches and fronds to producefiber. Utilization in the form of particle board using oil palm trunk. From basic research on the utilization of oil palm trunk, then it needs tools to process oil palm trunk into raw material that will be processed to be particle board, paper materials and cattle food. There are several steps to design a shredder machinei.e DFMA methods for determining the shredder machine design with easy assembly and manufacture, calculations to determine the motor power is using, and the simulation of structural strength testing using Autodesk Inventor to get the value of the safety factor of the frame and the shaft. The results obtained efficiency values assembly design is 3.14% .Then, the calculation results of the machine element motor power required is 3 Hp at 1400 rpm rotation for oil palm trunk with a surface area of 1 cm x 10 cm. The analysis result of the frame structure and shaft used Autodesk Inventor to obtain the safety factor value of the frame is 6.41 and the shaft is 4.3.Keywords: DFMA, Shredder Machine, Oil Palm Trunk, Safety Factor, Assembly Efficiency.